2009
DOI: 10.1017/s0016672309990176
|View full text |Cite
|
Sign up to set email alerts
|

Segregation distortion detected in six rice F2populations generated from reciprocal hybrids at three altitudes

Abstract: This paper presents investigations of segregation distortion of six rice F2 populations generated from reciprocal F1 hybrids grown at three locations varied at altitudes from 400 to 2200 m. The F1s were derived from reciprocal crosses between cv. XMG, which is a japonica landrace traditionally grown at 2650 m altitude, and cv. N34, which is a japonica restorer possessing a fertility restoring (Rf) gene and cytoplasm of male sterility (CMS) donated by an indica cultivar. Among nine morphological traits of the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 49 publications
6
12
0
Order By: Relevance
“…The direction of the distortion was selectively biased to F344 homozygotes in the WKY cytoplasm. In rice, Wang et al (2009) found that the japonica cytoplasm did not cause any distortion favouring a special parent, but that the indica cytoplasm favoured the maternal parent, which suggested that the indica cytoplasm was incompatible with a japonica nuclear background and that the japonica cytoplasm did not have such trouble with the indica nuclei. These results suggested that one of the cytoplasms in each case favoured the nucleus allele originating in the other inbred line and that the other cytoplasm showed no consistent bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The direction of the distortion was selectively biased to F344 homozygotes in the WKY cytoplasm. In rice, Wang et al (2009) found that the japonica cytoplasm did not cause any distortion favouring a special parent, but that the indica cytoplasm favoured the maternal parent, which suggested that the indica cytoplasm was incompatible with a japonica nuclear background and that the japonica cytoplasm did not have such trouble with the indica nuclei. These results suggested that one of the cytoplasms in each case favoured the nucleus allele originating in the other inbred line and that the other cytoplasm showed no consistent bias.…”
Section: Discussionmentioning
confidence: 99%
“…In invertebrates, Sinkins (2011) found a new embryo-killing gene that causes post-segregation distortion. In addition, mapping populations, genetic transmission, non-homologous recombination, gene transfer, transposable elements, reproductive isolation, environmental agents and non-biological factors, such as sample size, marker type and genotyping errors, are all possible causes for the observed segregation distortion (Xu et al, 1997;Wang et al, 2009;Phadnis, 2011). However, the most promising explanation is viability selection occurring at the markers or loci linked to the markers observed to have distorted inheritance (Vogl and Xu, 2000).…”
mentioning
confidence: 99%
“…have been reported in a number of plants such as rice (Wang et al 2009), and therefore detection of SDRs in the two populations developed from the two wild parental lines is a common feature more so among the F 2:3 population. It is assumed based on Mendelian law that there is an equal probability of transmission of alleles from either parent during sexual reproduction, but this has not been the case in several studies, being there tend to be phenomena referred to the preferential transmission of alleles or genotypes known as segregation distortion (SD) (Nadeau 2017).…”
Section: Several Gametophytic and Zygotic Barriers Causing Deviation mentioning
confidence: 99%
“…Rice consists of two major subspecies, indica and japonica, which were respectively designated as "Hsien" and "Keng" in China approximately 2,000 years ago (Ouyang et al, 2009). Abundant genetic diversity between subspecies, or ecotypes derived from different geographical environments, or ecotypes with different characteristics have led to numerous rice varieties worldwide (Wang et al, 2009). The indica and japonica subspecies vary in many important aspects during their growth and development process, including leaf color, apiculus hair length, and grain shape (Ouyang et al, 2009).…”
Section: Introductionmentioning
confidence: 99%